Dose conversion of radon exposure according to new epidemiological findings - Tomasek, L; Rogel, A; Laurier, D; Tirmarche, M (Radiation protection dosimetry, 2008)
In 1993, ICRP-65 recommended that dose conversion of radon exposure should be based on the comparison of detriments between radon exposure and effective dose. The lifetime detriment from the radon exposure was projected according to the epidemiological studies of uranium miners then available. The projection model (GSF) was multiplicative with temporal and age-at-exposure modification. Since 1993, new studies of uranium miners have appeared and many original studies were updated. In addition, projections of the risk have been improved by including further modifying factors as for instance in BEIR VI. New analyses were completed in the Czech and French studies of uranium miners with accurate estimates of exposures based on extensive radon measurements. The resulting estimates of excess absolute lifetime risk per unit exposure in working level months (WLM) from these models lead to dose conversion of 10 mSv WLM(-1) for the BEIR VI model and 8 mSv WLM(-1) for the joint Czech-French model in contrast to the conversion of 5 mSv WLM(-1) for the GSF model.
Keywords: Occupational Exposure; nádory plic; Lung Neoplasms; Humans; analýza přežití; Computer Simulation; Models, Biological; rizikové faktory; internacionalita; Internationality; lidé; Neoplasms, Radiation-Induced; Survival Analysis; Mining; nádory vyvolané zářením; radon; počítačová simulace; hornictví; dávka záření; pracovní expozice; incidence; Incidence; biologické modely; Radiation Dosage; Risk Assessment; míra přežití; Radon; hodnocení rizik; Risk Factors; Survival Rate